Teacher Assistance in Increasing Potential-based Student Learning Interest through the Implementation of Differentiated Learning at SMPN 1 Padalarang - H. Soro, Suharyanto; Fatimah, Siti; Novianna Darwis, Ira; Anggraeni Kusnadi, Andini; Candrawinata, Lalan (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Differentiated learning is an instructional approach designed to address the diverse needs of students, considering their varying levels of readiness, interests, talents, and learning styles. Challenges such as low student engagement and the limited capacity of teachers to adapt instructional materials have been identified as key issues. This Community Service Program aims to assist teachers at SMPN 1 Padalarang in developing and implementing differentiated learning strategies, promoting student-centered activities and improving student engagement. The program employs a service-learning approach, structured into three phases: preparation, which includes partner location surveys and module development; service delivery, involving theoretical socialization, group discussions, and classroom mentoring; and reflection, which entails academic assessments, satisfaction surveys, and evaluation reporting. The results of this community service initiative indicate a significant improvement in the knowledge and insights of the teachers at SMPN 1 Padalarang, West Bandung Regency, with 95% of participants demonstrating a comprehensive understanding of differentiated learning implementation in the classroom. Additionally, the teachers showcased enhanced skills in designing Lesson Plans (RPP) that integrate differentiated learning in terms of content, process, and products, achieving an average success rate of 90%. Furthermore, a Discussion Group Forum focused on differentiated learning was established, providing a platform for continuous professional development. Notable outcomes also include the selection of lead teachers for differentiated learning and the initiation of a monthly program by the Subject Teachers Association (MGMP) aimed at reflecting on and setting learning goals based on differentiated instruction principles.